Panggilan Orang Percaya dalam Berapologetika - Mukti, Guntur Hari (Sekolah Tinggi Teologi Kharisma, 2020)
The calling of faith as a believer has a lot of emphasis on being a witness for many people, so that through life's testimony many people become attracted to and believe in the Savior of the Lord Jesus Christ. The calling of apologetics in the life of faith is forgotten and as if it is only a part of those who get the title